P Perangkat Pembelajaran Terintegrasi Etnomatematika Permainan Tradisional untuk Meningkatkan Pemahaman Konsep Matematis - Devian, Lora; Ahmad Fauzan; Syafri Ahmad; Melva Zainil; Nevi Novelita (Jurnal Pendidikan dan Pengajaran, 2024)
Understanding of mathematical concepts is different than expected. Students need help learning mathematical concepts. Based on this, this research aims to develop an integrated learning tool for the ethnomathematics of traditional games. This type of research uses the Plomp development model with three stages. Subjects in this development research include instrument validators, expert validators (2 material experts, 1 language expert, and 1 cultural expert), teachers as expert practitioners, and third-grade students in three elementary schools. The methods used in collecting data were observation, interviews, questionnaires and tests. Data collection instruments are questionnaire sheets and test questions. Data analysis techniques were carried out qualitatively and quantitatively, as well as inferential statistics. The research results are validation results from experts in the very valid category. Second, the practical results of students are in the convenient category. Third, the results of teacher practicality are in the convenient category. The results of the N Gain score test show increased learning outcomes by developing an integrated worksheet on ethnomathematics on whole numbers counting operations to understand mathematical concepts in class III elementary school students. It was concluded that the integrated learning tools for ethnomathematics in the operational material for calculating whole numbers were valid and practical for increasing the understanding of mathematical concepts for class III elementary school students. This research implies that the traditional game ethnomathematics integrated learning tools developed can be used in learning.